Interpreting motif and pattern in Mohd Nor Mahmud painting batik: pakai semutar kain lepas / Haslinda Abd Razak, Rafeah Legino and Baharim Samuri - Abd Razak, Haslinda; Legino, Rafeah; Samuri, Baharim (2016)
This study was analyzed based on the visual characteristic illustrated on Mohd Nor Mahmud’s painting. The artwork of Pakai Semutar Kain Lepas was inspired from the traditional Malay batik design. Visual analysis approach was chosen and highlighted through the application of line, shape, texture, balance, repetition and space. Indeed, the analysis discovered that the artwork expended with verities of motifs design, which harmonized a unique pattern. The results were also stated about seventeen motifs that were formed from the floral and pucuk rebung (bamboo shoots) motif. In fact, the composition was significantly composed based on five vertical panels within the landscape format. This painting was one of the artwork that was created through batik methods. This approach is actually an option in how batik was explored into fine art practice and was displayed in a gallery.